2.6k views
2 votes
What is a simple way to solve for the sum and difference of 2 cubes? For example, 27+64
x^3 and 64
m^3-1

1 Answer

2 votes

Answer:

(3 + 4x)(9 - 12x + 16x²) = 0

(4m - 1)(16m² + 4m + 1) = 0

Explanation:

Here we have to solve the sum of two cubes which is
27 + 64x^(3)

Now, the equation is
27 + 64x^(3) = 0

⇒ 3³ + (4x)³ = 0

⇒ (3 + 4x)[3² - 3(4x) + (4x)²] = 0

(3 + 4x)(9 - 12x + 16x²) = 0

So, (3 + 4x) = 0 or (9 - 12x + 16x²) = 0

Therefore, from the above two relation we can solve for x.

One root will be
- (3)/(4) and the others we will get by applying Sridhar Acharya Formula, which will give a pair of conjugate imaginary roots of the equation.

Again, we have to solve the difference of two cubes which is
64m^(3) - 1

Now, the equation is
64m^(3) - 1 = 0

⇒ (4m)³ - 1³ = 0

⇒ (4m - 1)[(4m)² + 4m(1) + 1²] = 0

(4m - 1)(16m² + 4m + 1) = 0

So, (4m - 1) = 0 or (16m² + 4m + 1) = 0

Therefore, from the above two relation we can solve for m.

One root will be
(1)/(4) and the others we will get by applying Sridhar Acharya Formula, which will give a pair of conjugate imaginary roots of the equation. (Answer)

User Fredefl
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.